Precarious connections: Making therapeutic production happen for malaria and tuberculosis. (March 2015) - Craddock, Susan
Abstract: The One Health Movement has been a primary advocate for collaboration across disciplinary and organizational sectors in the study of infectious diseases. There is potentially much to be gained by incorporating the interrelations of animal and human ecosystems, as well as the expertise of veterinary, medical, and public health practitioners. Too often, however, the idea rather than the realities of collaboration become valorized within One Health approaches. Paying little to no attention to the motivations, ontologies, and politics of collaborative arrangements, however, is a critical mistake, one that diminishes considerably One Health framework explanatory powers. Using Anna Tsing's framework of friction, in this paper I take the examples of malaria and tuberculosis pharmaceuticals collaborations, often called Product Development Partnerships, to argue for the need to attend to the conditions under which collaborations across divergent disciplines, geographies, organizations, and institutions might work productively and when they do not. Highlights: Explores complexities of connection in research partnership actors. Uses Anna Tsing's framework of friction to examine PDPs for tuberculosis and malaria. Critiques limits of One Health approaches to examining responses to health problems.